2019
DOI: 10.1002/polb.24899
|View full text |Cite
|
Sign up to set email alerts
|

Properties of conductive polymer hydrogels and their application in sensors

Abstract: Conductive polymer hydrogels (CPHs), which combine the unique advantages of hydrogels and organic conductors, have received wide attention due to their adjustable mechanical properties, biocompatibility, self‐healing, hydrophilicity, and ease of preparation. With doping engineering and incorporation with other functional nanomaterials, CPHs have exhibited excellent physical/chemical properties. CPHs have been widely used in various electronic devices, especially in the field of sensors due to its sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 136 publications
0
75
0
Order By: Relevance
“…[225,227] Several types of conductive fillers are commonly used to formulate conductive inks, such as metal nanomaterials, [105,241,301] liquid metal, [84,227] carbon-based nanomaterials, [67,302] and conjugated polymers. [303][304][305] The thin-film conductive network could achieve high transparency, [105] whereas 3D percolation networks embedded inside polymer matrices are usually opaque. [306]…”
Section: Conductive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[225,227] Several types of conductive fillers are commonly used to formulate conductive inks, such as metal nanomaterials, [105,241,301] liquid metal, [84,227] carbon-based nanomaterials, [67,302] and conjugated polymers. [303][304][305] The thin-film conductive network could achieve high transparency, [105] whereas 3D percolation networks embedded inside polymer matrices are usually opaque. [306]…”
Section: Conductive Materialsmentioning
confidence: 99%
“…The volatile additive has also been applied to further enhance the mechanical performance of PEDOT:PSS. [305,398] Lu et al developed a high-performance PEDOT:PSS hydrogel with interconnected networks of PEDOT:PSS nanofibrils [277] (Figure 3k,l). Volatile additive dimethyl sulfoxide (DMSO) was mixed into the aqueous PEDOT:PSS with successive processes of controlled dry annealing and rehydration.…”
Section: Conjugated Polymersmentioning
confidence: 99%
“…[ 1–6 ] Owing to the feasibility of multiple patterning, the GLMAs have been endowed with superior reconfigurability, providing a promising route for the realization of the next generation wearable electronics, transient devices, soft robotics, biomedical sensing, and health monitoring. [ 7–11 ] Dickey et al [ 12,13 ] and Lee et al [ 14 ] demonstrated stretchable or pressure sensors by virtue of the pressure‐dependent resistance change of GLMAs. Considering of the self‐adaptability of liquid metal, Dickey et al [ 15 ] developed self‐propelled LM droplets that led to the self‐destructing of the circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been recently devoted to fabricating electrically conductive hydrogels as advanced strain sensors due to their outstanding flexibility, stretchability, and self‐healing properties. [ 28–29 ] Hydrogels are generally highly absorbent polymer networks that can accommodate large amount of water (more than 90%). With the availability of a broad range of environmentally benign natural or synthetic polymer materials for making the hydrogel networks, hydrogel‐based strain sensors offer good biocompatibility for human motion detection (i.e., friendly to human skin).…”
Section: Introductionmentioning
confidence: 99%